Macroeconomic and microeconomic determinants of non performing loans in the Italian Banking system - Plahuta, Giacomo (2018)
During the last years, we witnessed a gradual decline of bank’s assets quality. One of the best tools used in order to estimate the economy state of health is the level of non performing loans (hereinafter, NPLs). The first part of this study is focused on the Italian banking system and the results are consistent with the existent literature (Greece, Spain, etc.) showing an important impact of GDP, unemployment rate, size and solvency variables. The second section investigates on the impact of the crisis without any remarkable finding. The last one identifies big banks as more affected by NPLs level.